Doing qualitative research in a digital world - Paulus, Trena M.; Lester, Jessica Nina (SAGE, 2022)
"While some qualitative methods texts touch upon online communities as a potential data source, show how to conduct interviews and focus groups online, or address how to select recording devices and analysis software, no book has guided readers in the creation of a comprehensive digital workflow for their research until now. By working through each chapter in this book, readers will be able to generate a unique digital workflow for designing and implementing their research. The text provides a deep exploration of the relationship between theories of technology, substantive theories, and methodological theory, and shows ho together these inform the development of a quality research design. The authors include vignettes--narratives written by qualitative researchers describing cutting-edge use of digital tools and spaces--and also give examples of published studies, which together provide practical illustration of the content. Woven throughout is explicit attention to ethical challenges that are likely to be faced by researchers when adopting digital tools. The book invites readers to engage in a critical appraisal of the role of technology in qualitative research through reflection, conversation, and engagement with the larger community of researchers"--Page 4 of cover.